2022
DOI: 10.1093/brain/awac082
|View full text |Cite
|
Sign up to set email alerts
|

Defective lipid signalling caused by mutations inPIK3C2Bunderlies focal epilepsy

Abstract: Epilepsy is one of the most frequent neurological diseases, with focal epilepsy accounting for the largest number of cases. The genetic alterations involved in focal epilepsy are far from being fully elucidated. Here, we show that defective lipid signalling caused by heterozygous ultra-rare variants in PIK3C2B, encoding for the class II phosphatidylinositol 3-kinase PI3K-C2β, underlie focal epilepsy in humans. We demonstrate that patients’ variants act as loss-of-function alleles, leading to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…S4 C and D ) suggest that PI3KC2β may act on a different pool of 3-phosphoinositides, e.g., via synthesis of PI(3,4)P 2 ( 16 , 19 ). To test this we capitalized on a class III-like mutant version of PI3KC2β, which is selectively defective in PI(3,4)P 2 synthesis but can generate PI(3)P with WT efficacy ( 16 , 41 ). Strikingly, reexpression of mutant class III-like PI3KC2β failed to restore normal levels of β1-integrins in HeLa cells depleted of the endogenous enzyme ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4 C and D ) suggest that PI3KC2β may act on a different pool of 3-phosphoinositides, e.g., via synthesis of PI(3,4)P 2 ( 16 , 19 ). To test this we capitalized on a class III-like mutant version of PI3KC2β, which is selectively defective in PI(3,4)P 2 synthesis but can generate PI(3)P with WT efficacy ( 16 , 41 ). Strikingly, reexpression of mutant class III-like PI3KC2β failed to restore normal levels of β1-integrins in HeLa cells depleted of the endogenous enzyme ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Germline or somatic mutations in components of PI3K family are frequent in congenital vascular disorders, with mTOR signaling playing a central role in such pathogenesis ( 4 ). Ultra-rare variants in PIK3C2B cause focal epilepsy in humans ( 43 ), and on the basis of our data, it is tempting to speculate that these patients also have a predisposition to develop vascular anomalies, perhaps in an epistatic context. This may be relevant to some patients with vascular malformations associated with high PI3K/mTORC1 signaling for which the genetic cause is unknown ( 4 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 75%
“…Nesrin et al [ 37 ] showed that PIK3C2B (Phosphatidylinositol-4-Phosphate 3-Kinase Catalytic Subunit Type 2 Beta) could trigger specific muscle ablation and is identified as a genetic modifier of MTM1 mutation, and here we know that mutation of MTM1 is the cause of myotubular myopathy. On the other hand, some studies have confirmed that heterozygous ultrarare variants in PIK3C2B could cause defective lipid signals [ 38 ]. According to these findings, the changes in muscle and fat in vivo may be related to the differential expression of PIK3C2B .…”
Section: Discussionmentioning
confidence: 99%